A Three‐Dimensional Confined Crystallization Strategy Toward Controllable Growth of High‐Quality and Large‐Area Perovskite Single Crystals. (23rd March 2022) - Sun, Yuye; Liu, Xinyue; Deng, Wei; Zhang, Xiujuan; Lu, Zhengjun; Chang, Zhizhen; Fang, Xiaochen; Wu, Di; Jie, Jiansheng
Abstract: Large‐area organic–inorganic hybrid perovskite (OIHP) single crystals have attracted intensive interest for diverse device applications. However, conventional growth methods usually suffer from limited and disordered mass transport in the crystal growth process, making the large‐area fabrication of OIHP single crystals with controllable thickness remain a formidable challenge. Here, for the first time, a three‐dimensional confined crystallization (3DCC) strategy is reported to achieve centimeter‐scale growth of a OIHP single‐crystal array with tunable thickness. The 3D geometrical channels can not only induce an oriented capillary flow to enhance the mass transport by up to 100 folds, but also can effectively confine the crystal crystallization in both in‐plane and out‐of‐plane directions, thereby remarkably improving the crystallinity and thickness control of the crystals. Furthermore, a self‐driven lateral‐structured photodetector is demonstrated based on the resultant OIHP single‐crystal array with significant long‐term stability (>36 days, maintaining 80% of the initial performance) and outstanding device performance (linear dynamic range of 73 dB). The ability of the 3DCC strategy to scale up the growth of high‐quality perovskite single crystals opens a pathway for large‐scale and integrated optoelectronic applications. Abstract : A simple and scalable three‐dimensional confined crystallization (3DCC) strategy is developed to fabricate organic–inorganic hybrid perovskite single crystal arrays. This 3DCC approach not only enhances mass transport, but also effectively confines the crystal crystallization in both in‐plane and out‐of‐plane directions, enabling improvement of crystallinity over a large area as well as realization of accurate thickness control of the perovskite crystals.